NGHIÊN CỨU SỰ LƯU HÀNH VÀ KIỂU GEN CỦA VI RÚT VIÊM GAN B Ở MỘT SỐ ĐỊA PHƯƠNG GIAI ĐOẠN 2012-2013 - Dương, Tuấn Linh; Bùi, Thị Lan Anh; Phạm, Ngọc Quang; Đoàn, Trọng Tuyên; A.V., Dmitriev; O.V., Kalinina (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON PREVALENCE AND GENOTYPE OF HEPATITIS B VIRUSES IN SOME PROVINCES IN THE PERIOD 2012-2013The hepatitis B virus (HBV) is among the leading causes of chronic hepatitis, cirrhosis and hepatocellular carcinoma. Screening of 664 serum samples from Hoabinh, Quangtri, Kontum provinces and Ho Chi Minh city showed that the prevalence of HBsAg varied by geographic regions and gender. The highest one was in Hoabinh (18.27% in general, 21.95% in male, and 13.38% in female), and the lowest one was in Kontum (3.1% in general, 2.32% in male, and 4.32% in female). InVietnam, the most common genotype is B, followed by genotypes C and G.HBV phylogenetic analysis of S sequences revealed that genotype B was highly prevalent (83.3%), and genotype C (8.3%) and G (8.3%) were also detected as a minor distribution. Further studies are recommended to determine the HBsAg prevalence and genotypes and main modes of hepatitis B virus transmission in Vietnam.